2018
DOI: 10.1002/j.2769-2795.2018.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypoxic‐ischemic encephalopathy in neonates: a systematic review and meta‐analysis

Abstract: To investigate the clinical effectiveness of treatment with hypothermia, erythropoietin (EPO), hyperbaric oxygenation (HBO), xenon gas treatment, melatonin for neonates with hypoxic‐ischemia encephalopathy (HIE). A comprehensive searching work of related publications was carried out in the Pubmed and CNKI database. Those randomized controlled trials deemed eligible, which made comparisons between the therapies for neonates with HIE and the normal treatment. The continuous and dichotomous data were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To date, current strategies for clinical therapies involve anticonvulsants, hypothermia, electrolyte, and fluid management, as well as atropine and adrenaline applications. Nevertheless, there is still a lack of effective therapeutic approaches, primarily as a result of lacking mechanistic understanding of the pathophysiology of NHIE 7–9 . Therefore, the effective prevention and control measures in the study of the pathogenesis of NHIE should be urgently identified and developed 10–12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, current strategies for clinical therapies involve anticonvulsants, hypothermia, electrolyte, and fluid management, as well as atropine and adrenaline applications. Nevertheless, there is still a lack of effective therapeutic approaches, primarily as a result of lacking mechanistic understanding of the pathophysiology of NHIE 7–9 . Therefore, the effective prevention and control measures in the study of the pathogenesis of NHIE should be urgently identified and developed 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is still a lack of effective therapeutic approaches, primarily as a result of lacking mechanistic understanding of the pathophysiology of NHIE. [7][8][9] Therefore, the effective prevention and control measures in the study of the pathogenesis of NHIE should be urgently identified and developed. [10][11][12] Scutellarin is a natural herbal medicine, which has been shown to treat inflammation, allergy, and bacterial and viral infections.…”
Section: Introductionmentioning
confidence: 99%